Legal Study on The Role of The Government of The City of Batam in Distributing Land Perspective Welfare State - Maurice Rogers; Mhd Taufiqurrahman (LEGAL BRIEF, 2021)
Legal Studies on the Role of the Batam City Government in Distributing Land from the Welfare State Perspective. The purpose of this study is to examine the role of the Batam City government in distributing land in the Batam City area. Based on the formulation of the problem in compiling this research, the type of research used is normative or doctrinal legal research. Normative or doctrinal legal research is a legal research method that uses secondary data sources or by examining existing library materials. The nature of this research is descriptive analytical research. Analytical descriptive research is a form of research aimed at describing existing phenomena, both natural phenomena and man-made phenomena. Land problems in Batam City are like tangled threads that never end and are resolved, causing dissatisfaction in the people of Batam City. In the midst of the difficulty of access to adequate housing, while the need for housing is increasingly inevitable, finally a shortcut to establish a residence on State land that is not intended for settlement is the choice taken by some Batam people.